Educative management as a determining factor in the performance of regular basic education teachers during the COVID-19 pandemic, Puno-Peru. - Meza Revatta, Lucas Fernando (2020)
The objective of this research was to analyze the effect of educational management on the teaching performance of teachers of Basic Basic Education in the department of Puno, during the COVID-19 Pandemic. It corresponds to an investigation with a quantitative approach, explanatory scope and non-experimental design, which included the participation of 650 teachers from 10 Units of Local Educational Management, to whom a scale of perception of educational management and a self-assessment questionnaire of the teaching performance, both valid and reliable; The analyzes were performed based on a significance level of 5% and a confidence level of 95%. The results show a direct and significant correlation between the variable educational management and teacher performance (r = .623, p <.05), in the same way with the institutional management dimensions (r = .523, p <.05), Pedagogical management (r = .499, p <0.05), Administrative management (r = .611, p <.05) and Community management (r = .514, p <.05). In addition to this, the multiple linear regression model explains the effect that the educational management variable and its dimensions have on the teaching performance of teachers in Puno. It is concluded that educational management, which can be understood as the strengthening of Educational Projects and the enrichment of pedagogical processes in order to respond to local and regional educational needs, is a determining factor that explains the level of performance they achieve teachers of Regular Basic Education in Puno during the COVID-19 Pandemic.